2001
DOI: 10.1021/bi0109257
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Heme Ruffling and Bent NO Geometry in Ultra-High-Resolution Structures of Nitrophorin 4,

Abstract: The nitrophorins are a family of proteins that use ferric heme to transport nitric oxide (NO) from the salivary glands of blood-sucking insects to their victims, resulting in vasodilation and reduced blood coagulation. We have refined atomic resolution structures of nitrophorin 4 (NP4) from Rhodnius prolixus complexed with NO (1.08 A) and NH(3) (1.15 A), yielding a highly detailed picture of the iron coordination sphere. In NP4-NO, the NO nitrogen is coordinated to iron (Fe-N distance = 1.66 A) and is somewhat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
364
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(391 citation statements)
references
References 42 publications
25
364
0
2
Order By: Relevance
“…5 Biochemical and structural studies have revealed that heme distortion is correlated to changes in heme reactivity, ligand binding, and protein conformation. 5,14,[18][19][20][21]22,23 As observed in the structure reported here, disconnection of the heme and proximal helix in the H102G mutant results in a significantly relaxed heme cofactor conformation. A comparison of the heme cofactors shows that pyrroles A and D move away from the proximal side of the heme pocket toward the distal side in the H102G mutant compared with wild type [ Fig.…”
Section: Analysis Of the Heme-binding Pocketsupporting
confidence: 76%
“…5 Biochemical and structural studies have revealed that heme distortion is correlated to changes in heme reactivity, ligand binding, and protein conformation. 5,14,[18][19][20][21]22,23 As observed in the structure reported here, disconnection of the heme and proximal helix in the H102G mutant results in a significantly relaxed heme cofactor conformation. A comparison of the heme cofactors shows that pyrroles A and D move away from the proximal side of the heme pocket toward the distal side in the H102G mutant compared with wild type [ Fig.…”
Section: Analysis Of the Heme-binding Pocketsupporting
confidence: 76%
“…This conformational change introduces distortions to the heme group and causes the Fe-N-O structure to be bent. It was proposed that this unique heme environment stabilizes the NO and prevents autoreduction of the heme, which is very important for nitrophorin to perform its physiological function (33). Intriguingly, the Fe-NO stretching and Fe-N-O bending frequencies of nitrophorin determined by resonance Raman measurements were identical to those of the NO derivative of HbN (38), despite the fact that the distal pocket of nitrophorin is hydrophobic in contrast to the hydrophilic pocket of HbN (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…41,42 However, these measurements do not exclude other vibrations that may appear in this frequency range, such as the FeCO distortion mode (in-phase bend/tilt) in iron carbonyl porphyrins [43][44][45] or other heme distortions that may control redox reactions. 46,47 The weak sensitivity of low frequencies to isotopic substitution presents a significant obstacle to associating specific atomic motions with observed frequencies. In contrast, NRVS measurements on oriented single crystals definitively identify Fe motion orthogonal to the heme plane associated with low frequency modes in model compounds.…”
Section: Introductionmentioning
confidence: 99%